Digital Transformation and Strength of Auditing and Reporting Standards in African Countries: The Moderating Effect of Efficacy of Corporate Boards - Chaieb, Souad (Journal of Cultural Analysis and Social Change, 2025)
Purpose: this paper examines the relationship between the digital transformation and the strength of auditing and reporting standards (SARS) in African countries and tests whether the efficacy of corporate boards moderates this association. Design/methodology/approach: The sample includes 96 country-year observations over a period of 2015–2017. Data are gathered from the Global Competitiveness reports and the Word Bank for the same years. Findings: Findings show that the digital transformation is positively associated with the SARS. Similarly, when testing for the moderating effects of efficacy of corporate boards, the association between the digital transformation and the SARS remains positive and significant for settings characterized by high efficacy of corporate boards, while it becomes insignificant for countries characterized by low efficacy of corporate boards. Policy implications: The findings highlight the importance of digital transformation on the SARS in African countries and emphasize the critical role played by efficacy of corporate boards in strengthening this relationship.